Topical treatment of contact dermatitis by pine processionary caterpillar. (15th August 2011) - Cuevas, Pedro; Angulo, Javier; Giménez-Gallego, Guillermo
Abstract : Skin contact dermatitis by pine processionary ( Thaumetopoea pityocampa ) is a public health problem of increasing significance. The authors present here the case of a 65-year-old man who was diagnosed with processionary caterpillar dermatitis. Patient was treated with topical potassium dobesilate 5% cream twice a day for 2 days. An improvement occurred soon after treatment.